THE INFLUENCE OF CONTENT MARKETING, E-WOM, AND BRAND AWARENESS ON PURCHASE INTENTION OF EIGER PRODUCTS ON TIKTOK AMONG GENERATION Z - Ahmad Rosyidun Nafi’; Mochamad Rizal Yulianto; Andry Rachmadany (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Content Marketing, Electronic Word of Mouth (E-WOM), and Brand Awareness on the Purchase Intention of Eiger products among Generation Z on TikTok, focusing on identifying which factors most effectively drive consumer decisions in the digital-native segment. Method: A quantitative descriptive approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with data collected from 96 Generation Z respondents who actively use TikTok and have been exposed to Eiger promotional content. A purposive sampling method was applied, and measurements were conducted using a Likert-scale questionnaire based on established indicators for each variable. Results: The findings reveal that Brand Awareness significantly and positively influences purchase intention, while Content Marketing and E-WOM do not show a significant impact. The R-square value of 0.778 indicates that 77.8% of the variance in purchase intention can be explained by the tested variables, with brand awareness emerging as the dominant factor. Novelty: Unlike many prior studies highlighting the role of content marketing and E-WOM in driving Generation Z consumer behavior, this research demonstrates that on TikTok, purchase intention is primarily shaped by brand awareness. This highlights the strategic importance of enhancing brand presence, consistent messaging, and digital engagement to strengthen consumer trust and encourage purchasing decisions.